Application of Blended Learning Method in Learning Islamic Religious Education - Unik Hanifah Salsabila; Nur Rahmah Fitria; Wijiutami, Latifah Sapta; Rahayu, Astrid Nur; Anggi Pratiwi (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2024)
This study aims to determine how the blended learning method is applied in education, especially Islamic Religious Education, since the Covid-19 pandemic has changed the current educational landscape. The research method used in this study is library research, which refers to various sources to collect bibliographical data. This study's results will show that applying the blended learning method in education, especially Islamic Religious Education, is very important. Create a model that can later help foster the educational process using the blended learning method and have hopes of succeeding in the teaching and learning process. Therefore, in this article, we will discuss how to apply learning using the blended learning method for success in the learning process, both offline (face-to-face) and online models.